Within‐plant distribution of Phorodon humuli (Hemiptera: Aphididae) and natural enemies on hops with implications for sampling and management - Lorenzana, Alicia; Hermoso-De-Mendoza, Alfonso; Seco, Victoria; Campelo, Piedad; Casquero, Pedro A. (Wiley Online Library, 2020)
A field trial was performed on a hop yard throughout 2006, 2007 and 2008 in order to analyze the within‐plant distribution of Phorodon humuli (Schrank) and its natural enemies. The aphid population was higher on the leaves of the middle section of the main stem. Specifically, the population was significantly higher at 2 and 3.25 m than at 6 m during the three years. Natural enemies consisted of aphidophagous predators of which Coccinella septempunctata was recorded in the highest number. Its number was greater where the aphid population was higher, with a significantly higher number of eggs, larvae and adults at 2 and 3.25 m than at 6 m. Lacewing eggs were also frequently observed, with a significantly higher population where the number of aphids was higher. The number of winged aphids was higher at 3.25 m than at 2 m within a plant. Understanding hop aphid distribution within the hop canopy is important in developing sampling programs, in evaluating injury and helps the development of sustainable management practices.